Photodegradation of Direct Violet 51 Dye using Bi2MoO6 /GO Nanoflakes as Promising Solar Light-driven Photocatalyst: Photodegradation of Direct Violet 51 dye - Sumaira Younis; Haq Nawaz Bhatti; Sadia Z. Bajwa; Jie Xu; Saba Jamil (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Water contamination is a challenging issue for the maintenance of environmental sustainability. Industrial effluents are considered major sources of water pollution which affect the quality of surface as well as ground water. In the present research work, semiconducting Bismuth Molybdate/Graphene Oxide (Bi2MoO6/GO) composite nanomaterial has been introduced as the solar light-driven catalyst for photodegradation of Direct Violet (DV) 51 dye and industrial wastewater. Scanning electron microscope (SEM), zeta potential, X-ray diffraction analysis and Fourier transform infrared spectroscopy (FTIR) were used to characterize the Bi2MoO6 /GO composite material. Experimental findings revealed that flake-like Bi2MoO6 /GO composite exhibits 99.00 % degradation activity against DV dye within 80 minutes. Bi2MoO6 /GO nanoflakes degrade DV dye up to 98.70 % at pH 7 and 99.99 % with a 100 mg catalyst dose within 60 minutes, respectively. The stability/reusability study presented 99.82 % - 93.84 % dye degradation from the 1st to 7th day within 80 minutes while optimizing experimental parameters. According to kinetic studies of experimental outcomes, the pseudo-first-order model was best fitted to the obtained data with a coefficient of determination R2=0.954. Moreover, a 69.23 % reduction was observed in chemical oxygen demand (COD) during the photodegradation study of industrial wastewater. Results indicate that Bi2MoO6 /GO nanoflakes have good photocatalytic potential and stability to degrade organic water pollutants under sunlight. Such materials can be used effectively for the photodegradation of organic water pollutants to enhance environmental safety.